Taxa de juros e desenvolvimento no Brasil: o caso dos bancos privados e o papel do setor público - Ramos, Vânia Vieira (2012)
The interest rate is one of the main instruments of monetary policy for the control of the economy, especially for that countries, like Brazil, that use the Inflaction Target System. Brazil presents one of the world's highest interest rates. This hampers the development and the heating of the economy as a whole, as the credit takers, individuals and legal entities, especially those considered "good payers", feel discouraged to seek for financial institutions, because the charge to be paid at the end of a contract of credit is exorbitant. Moreover, the inertia of high interest rates of the Brazilian banking system led foreign banks with branches here, to the same behavior of domestic banks, and this behavior does not bring stimulus to the credit, as not brought competitiveness for the Brazilian banking sector. In this regard, this work tries to make a comparative study between high interest rates used in Brazil, by private domestic and foreign banks, and public national banks, with the latter, are financial institutions that have political, economic and social conditions to drive a significant drop in interest rates and stimulate development. The first chapter is the Theoretical Framework, it sought to understand the concept of economic development and its relationship with credit. The second chapter is a historical chapter on the interest rate practiced in Brazil from 1990 to 2010. This chapter, aimed to build a history of the Brazilian interest rate, making a comparison between the interest rates charged by major private banks (domestic and foreigners) - Bradesco, Itau, Banco Santander and HSBC in Brazil, U.S., Spain and England. In this same chapter we tried to investigate what the main impacts of the practice of high interest rates on the Brazilian economy. And at the end of this chapter, held a brief study of the legal issue behind the high interest rates in place in Brazil today. The third chapter is called: National Public Banks: Solutions with Subsidized Interest Rate and Microcredit, and seeks to understand the role of public banks in the lending scenario in Brazil. To this end, we evaluated case by case, the main role of public institutions providing credit. Among the key findings, we have that foreign banks has not pushed down the interest rate as was assumed when the financial openness. This role falls to the national public banks which, in the Brazilian context, possess sufficient market power to exert influence on the final interest rate and spread, thus ensuring the efficient transmission of monetary policy